Accelerating cine phase-contrast flow measurements using k-t BLAST and k-t SENSE - Baltes, Christof; Kozerke, Sebastian; Hansen, Michael S.; Pruessmann, Klaas P.; Tsao, Jeffrey; Boesiger, Peter (Magnetic resonance in medicine, 2005)
Conventional phase‐contrast velocity mapping in the ascending aorta was combined with k‐t BLAST and k‐t SENSE. Up to 5.3‐fold net acceleration was achieved, enabling single breath‐hold acquisitions. A standard phase‐contrast (PC) sequence with interleaved acquisition of the velocity‐encoded segments was modified to collect data in 2 stages, a high‐resolution undersampled and a low‐resolution fully sampled training stage. In addition, a modification of the k‐t reconstruction strategy was tested. This strategy, denoted as “plug‐in,” incorporates data acquired in the training stage into the final reconstruction for improved data consistency, similar to conventional keyhole. “k‐t SENSE plug‐in” was found to provide best image quality and most accurate flow quantification. For this strategy, at least 10 training profiles are required to yield accurate stroke volumes (relative deviation <5%) and good image quality. In vivo 2D cine velocity mapping was performed in 6 healthy volunteers with 30–32 cardiac phases (spatial resolution 1.3 × 1.3 × 8–10 mm3, temporal resolution of 18–38 ms), yielding relative stroke volumes of 106 ± 18% (mean ± 2*SD) and 112 ± 15% for 3.8× and 5.3× net accelerations, respectively. In summary, k‐t BLAST and k‐t SENSE are promising approaches that permit significant scan‐time reduction in PC velocity mapping, thus making high‐resolution breath‐held flow quantification possible. Magn Reson Med, 2005. © 2005 Wiley‐Liss, Inc.